Theorizing the behavioral state: Resolving the theory-practice paradox of policy sciences. (April 2022) - Leong, Ching; Howlett, Michael
Traditionally, the policy sciences exhibited a paradoxical relationship to public behavior: arguing in theory that it was rational in a utilitarian sense and could be modelled as such while at the same time recognizing its irrational nature in practice without attempting to reconcile this contradiction. A recent behavioral turn among policy scholars has broken the discursive hegemony of traditional hedonic compliance-deterrence models, however, placing informal institutions such as norms, irrationalities and collective action at the center of the policy research agenda. To date there has been little theorizing of the implications of this turn for the policy-making nature of the state, as well as its extent and nature. Addressing these gaps we conduct a bibliometric review, which finds that the number of behaviorally-oriented articles on policy instruments have been increasing in number and relevance. This provides evidence of a behavioral turn in policy studies as well as documenting the emergence of a behavioral state, that is one which is more inclined to reconcile policy-making theory and practice by embracing the irrationalities of policy actors, through the creation of nudge and behavioral units across a wide range of domains, a shift in emphasis from the supply of policy to the demands of policy targets. However, the study shows the impact of this turn is geographically and sectorally uneven and will become more generalized in the future only if more states embrace this 'turn'.